Integrating the Participants' Perspective in the Study of Language and Communication Disorders Towards a New Analytical Approach - Klemmensen, Charlotte Marie Bisgaard (Springer International Publishing, 2018)
This book presents a new analytical approach that will advance the establishment of a new discourse within the study of language and communication disorders. Instances of recurring aphasia and acquired brain injury are discussed in an empirical observation study through a theoretical lens that combines Integrational Linguistics, ethnomethodology, Conversation Analysis and practice theory. In doing so, this interdisciplinary analysis adds a person-centered perspective to existing ethnographic approaches. It addresses a significant gap in our understanding of the social/communicative/interactional consequences of brain injury for everyday life by focusing on the practical problems that individuals with communication difficulties and acquired brain damage - and their care-takers, family and friends - have to solve in everyday life, and how they solve them. This innovative work will appeal to health and social care practitioners and care-givers, in addition to scholars of health communication, cognitive, psycho- and sociolinguistics. Charlotte Marie Bisgaard Klemmensen is a researcher in Communication and Psychology at Aalborg University, Denmark.